Peran Gembala Jemaat dalam Pengajaran Agama Kristen terhadap Keterlibatan Warga Jemaat dalam Pelayanan - Rotua Julianovia Hutagalung; Romi Lie (Didache: Journal of Christian Education, 2021)
Lack of church involvement in every church activity (service), because the congregation does not get guidance, direction, and teaching. If Christian religious teaching is taught properly and healthily, the congregation will be strong / survive, experience a change in thinking (cognitive), attitude (affective), and willing to be involved (psychomotor) in church activities. That is why, if the congregation has received formation, teaching properly and healthily, they will take root, grow, and bear fruit (Colossians 3:17). The method presented during the study was to use quantitative methods, namely distributing questionnaires to members of the Church of Christ Rahmani Indonesia, Sola Gratia Church, Ruko Permata Ujung Menteng. As a result, as a pastor, the task is not only to shepherd but also to be responsible for the spirituality of the church in providing teaching, formation, direction, and training to church members.